THE ANTIBACTERIAL ACTIVITY OF NIGELLA SATIVA AGAINST MULTI-DRUG RESISTANT PSEUDOMONAS AERUGINOSA ISOLATED FROM DIABETIC WOUND INFECTIONS - El-Shouny, Wagih A; Ali, Sameh S; Fayed, Shymaa F (MATTER: International Journal of Science and Technology, 2016)
Thirty-five specimens were isolated from diabetic patients with superficial and deep wounds. The isolates of Pseudomonas aeruginosa were selected from cetrimide agar plates supplemented with nalidixic acid.P. aeruginosawere subjected to in vitro evaluation of antibiotic sensitivity test using antibiotics from different classes. Multi-drug resistant P. aeruginosa (MDRPA) were selected for further tests and multiple antibiotic resistance (MAR)index was calculated. Eleven commercial essential oils (EOs) were chosen to evaluate their activities as antimicrobial agents against MDRPA. The sensitivity was determined using agar disc diffusion method. The black seed oil (Nigella sativa) showed a wide spectrum of inhibition against MDRPA3. The characterization of Nigella sativa was conducted by GC-MS and FT-IR which showed the antibacterial activity and safety of this oil.